Diabetes Risk by Length of Residence among Somali Women in Oslo Area - Abdi A. Gele; Kjell Sverre Pettersen; Bernadette Kumar; Liv Elin Torheim (Journal of Diabetes Research)
Type 2 diabetes represents a major health problem worldwide, with immigrants strongly contributing to the increase in diabetes in many countries. Norway is not immune to the process, and immigrants in the country are experiencing an increase in the prevalence of diabetes after arrival. However, the dynamics of these transitions in relation to the duration of residence in the new environment in Norway are not clearly understood. From this background, a cross-sectional quantitative study using a respondent-driven sampling method was conducted among 302 Somali women living in Oslo area. The results show that 41% of the study participants will be at risk for developing diabetes in the coming 10 years, which coincides with 85% of the study participants being abdominally obese. Significant associations were found between years of stay in Norway and the risk for diabetes with those who lived in Norway >10 years, having twofold higher odds of being at risk for developing diabetes compared to those who lived in Norway ≤5 years (OR: 2.16, CI: 1.08–4.32). Understanding the mechanisms through which exposure to the Norwegian environment leads to higher obesity and diabetes risk may aid in prevention efforts for the rapidly growing African immigrant population.